Appositive Preceedingand Delaying Between Noun Sentence Elements And Their Indication In The Holy Quran - الجفّان , عبد العزيز احمد (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
This study deals with the impedance of introducing and delaying the noun sentence elements in the Noble Qur’an in an attempt to clarify its concept and importance. As introduction and delay are one of the means of producing meaning, and it is subject to the intentionality of the speaker, and his will to express the meanings latent within him and what he wants to convey; So you see it as more subject to meaning. Because the syntax in the language has certain patterns, as for the choice and the method, it is subject to the intention of the speaker for a rhetorical or informative purpose; Each difference in the order of the sentence entails a difference in the meaning, just as the arrangement and its importance in performing the meaning is subject to the context and its indication of the position contained in it. . The purpose of the presentation and the delay is determined according to the intent of the speech. The presentation is related to the positions. The presentation and the delay may be due to the care and attention, that is: what you presented I mean, and maybe it was for the competence, and the interest does not mean to provide what is better and more honorable. Take into account the aspect of pronunciation and meaning. And the speaker introduces, delays and arranges his words according to their meanings without submitting to the language system; Because it intends to freedom of expression in order to convey its meanings to the recipient, and this allows him to deviate from the original established expansion rather than an anomaly, which is what we call the symptoms of the sentence. The research was divided into three parts, which are: He opposed presenting the news to the initiator, opposed the presentation of the news of the missing actions in its name, and he opposed the presentation of the news of the similar letters in its name. Trying to simplify opinions as possible.